Spectrographic Observations of Speech of an Ataxic Dysarthric - Nataraja NP; Indira Nandyal (Journal of All India Institute of Speech and Hearing, 1970)
Speech is a motor act. Speech results from th e fine coordination of various speech  muscles. Motor areas in cerebral  hemispheres, cerebellum and other lower centres have been considered to be controlling this motor activity. 'Co-ordination  of  movements  and maintenance of balance and muscle tones are dependen t on th e cerebellum and its connections' (Mysak, 1976).